Comparison of the Ecological Value of Sacred and Nonsacred Community Forests in Kaboli, Togo. (February 2018) - Lynch, Lauren; Kokou, Kouami; Todd, Susan
Despite Togo's naturally low forest cover and high rates of deforestation, remnant forest patches play an important role in conserving biodiversity and ensuring the well-being of the country's human population. Many of these remnant forest patches are sacred forests, ecosystems that are increasingly threatened because of changes in belief systems which have accompanied westernization. This study compares the ecological value and level of degradation of two sacred forests with an otherwise similar control forest that does not contain a sacred site based on characteristics including tree cover, vegetation composition, biodiversity, and biomass. The sacred forests had a significantly higher percentage of tree cover, higher biodiversity, and a greater biomass than the forest that did not contain a sacred site. In addition, dominant species within the sacred forests were associated with deciduous dry forest ecosystems while dominant species within the forest not containing a sacred site were introduced plantation species and species associated with savanna ecosystems. These results indicate that sacred forests in Kaboli, Togo, have a higher ecological value and are less degraded than similar community forests that do not contain a sacred site. This important role of sacred sites in forest conservation suggests that feedback loops exist between social and ecological systems, and that both need to be considered together to achieve effective development of forest conservation strategies.